Unilateral acne after facial palsy - Emilio Sudy; Francisco Urbina (Sociedade Brasileira de Dermatologia, 2018)
Abstract: We describe a case of unilateral acne which appeared after an episode of facial nerve palsy. An 18-year-old female patient presented with papules and pustules predominantly located on the side where the facial paralysis occurred. The patient suffered right facial paralysis, which was treated with prednisone and kinesiotherapy with massages, electrostimulation, and infrared light. Two weeks later, acne lesions appeared in the area affected by the paralysis. As suggested in other cases of paralysis, including cases of Parkinson's disease and spinal cord injury, an increased sebum excretion rate and the immobility of the affected area are most likely what caused the unilateral acne lesions.